DETERMINATION OF ENERGY LOSSES BY SHOCK ABSORBER IN A FREIGHT CAR AT CRASH MODE - Bolzhelarskyi, Ya. V.; Sobolevska, Yu. H.; Dovganyuk, S. S.; Batig, A. V. (Science and Transport Progress, 2016)
Purpose. The purpose of this work is to determine the energy losses in the shock absorber of the freight car whose wheel-set moves in the derailed state on the track panel depending on the axle load and structural parameters of spring suspension. Methodology. On the basis of spring suspension construction analysis and operating principle of the friction shock absorber of the freight car bogie the authors provide the method for determining the energy absorbed by it. The calculations take the maximum values of the absorber elements displacement and the regulatory values of spring suspension parameters. Findings. The authors obtained the calculated formula for determining the energy absorbed by shock absorber for regulation-set mounting schemes of elastic bogie elements depending on the axial load. The mentioned curves are parabolic. Originality. The work examines the crash mode of the wheel-set movement on the track panels after its derailment. It is shown that the energy dissipation in the shock absorbers is the reason for increase in resistance to rolling stock movement. The formulas for calculating the amount of energy dissipated in the shock absorber with a maximum displacement of its elements are derived. This energy depends on the axle load and structural parameters of spring suspension. Practical value. The proposed method allows setting the value of the additional resistance to motion that occurs in crash mode which makes it possible to increase the accuracy of traction calculations.